What is a fair amount of executive compensation? Outrage potential of two key stakeholder groups. (21st February 2018) - Arnold, Markus C.; Grasser, Robert
Abstract: The public discussion of executive compensation often centres on 'fair' and 'unfair' amounts and the public outrage over compensation that is deemed too high. The academic literature states that such outrage can lead to outrage costs, pressuring firms to adjust compensation levels. However, it is unclear what a 'fair' compensation is for various stakeholders and how their fairness concerns relate to outrage constraints. Based on surveys among two key stakeholder groups (representative eligible voters and investment professionals), we provide evidence that fairness is an important criterion for both groups but that opinions on how large a fair compensation amount should be are widely dispersed. Moreover, personality traits systematically influence fairness opinions through self‐serving interpretations of distributive justice and personal risk attitudes, indicating that a 'fair' amount of executive compensation may strongly depend on the involved stakeholders. Investigating thresholds for outrage, i.e., amounts above which compensation is judged 'unfairly' high, we show that even though investment professionals care for fairness as well, 'capital market outrage' might not equate to 'public outrage'. Our paper contributes to the literature on outrage constraints by linking individual fairness concerns to outrage potential and has implications for transparency of executive compensation and research on shareholder activism.